2009
DOI: 10.1162/jeea.2009.7.1.206
|View full text |Cite
|
Sign up to set email alerts
|

Herd Behavior in Financial Markets: An Experiment with Financial Market Professionals

Abstract: We study herd behavior in a laboratory financial market with financial market professionals. An important novelty of the experimental design is the use of a strategy-like method. This allows us to detect herd behavior directly by observing subjects' decisions for all realizations of their private signal. In the paper, we compare two treatments: one in which the price adjusts to the order flow in such a way that herding should never occur, and one in which the presence of event uncertainty makes herding possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 35 publications
3
63
0
1
Order By: Relevance
“…A path-breaking paper by Avery and Zemsky (1998) introduced efficient prices to a sequential herding context, but showed that in a simple financial market-trading setting with two values herding is not possible because the market price always separates people with good and bad information so that the former always buy and the latter always sell. Experimental work has confirmed these predictions (Drehmann, Oechssler, and Roider (2005), Cipriani and Guarino (2005), Cipriani and Guarino (2009)). More recently, however, Park and Sabourian (2011) showed that with multiple states herding can arise and they gave conditions on information that must be satisfied to admit rational herding; they also described conditions for rational contrarianism.…”
mentioning
confidence: 60%
“…A path-breaking paper by Avery and Zemsky (1998) introduced efficient prices to a sequential herding context, but showed that in a simple financial market-trading setting with two values herding is not possible because the market price always separates people with good and bad information so that the former always buy and the latter always sell. Experimental work has confirmed these predictions (Drehmann, Oechssler, and Roider (2005), Cipriani and Guarino (2005), Cipriani and Guarino (2009)). More recently, however, Park and Sabourian (2011) showed that with multiple states herding can arise and they gave conditions on information that must be satisfied to admit rational herding; they also described conditions for rational contrarianism.…”
mentioning
confidence: 60%
“…Speci…cally, one can consider a model in which subject 2 may have ambiguous beliefs on subject 1's rationality (along the line of the literature with multiple priors). 7 In such a case, as we anticipated in the Introduction, it is important to specify how a subject updates beliefs. For exposition motives, we …nd it convenient to postpone this discussion to Section 5, after we will have presented the main results.…”
Section: The Theoretical Modelmentioning
confidence: 99%
“…The experiment was programmed and conducted with a built-on-purpose software. 7 Another departure from Bayesianism would be to allow for ambiguity on the precision of signals. This would be a more far fetched hypothesis, since the composition of the urns is known.…”
Section: The Experimentsmentioning
confidence: 99%
“…Except in one case, which we attribute to chance, we never reject the null hypothesis that outcomes come from the same distribution (the results of these tests are reported in Appendix B). Therefore, we consider the three treatments as just 12 Cipriani and Guarino (2009) use a quasi strategy method, asking subject to make decisions conditional on either signal they might receive. Still, at each time, a subject never makes a decision based only on the predecessors' decisions.…”
Section: Experimental Designmentioning
confidence: 99%